2013
DOI: 10.1155/2013/928280
|View full text |Cite
|
Sign up to set email alerts
|

Anticancer Activity of Indian Stingless Bee Propolis: AnIn VitroStudy

Abstract: Indian stingless bee propolis has a complex chemical nature and is reported to possess various medicinal properties. In the present study, anticancer activity of the ethanolic extract of propolis (EEP) was explored by testing the cytotoxic and apoptotic effect in four different cancer cell lines, namely, MCF-7 (human breast cancer), HT-29 (human colon adenocarcinoma), Caco-2 (human epithelial colorectal adenocarcinoma), and B16F1 (murine melanoma), at different concentrations. Cytotoxicity was evaluated by MTT… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
48
0
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 73 publications
(51 citation statements)
references
References 25 publications
1
48
0
2
Order By: Relevance
“…In control group, cells were treated with just complete media. In Hcy group, cells were exposed to 50 mM Hcy [34] in complete media for 24 h. In cotreatment group, cells were incubated with 50 mM Hcy and 50 mg/ml propolis [35] in complete media for 24 h.…”
Section: Experimental Groupingmentioning
confidence: 99%
“…In control group, cells were treated with just complete media. In Hcy group, cells were exposed to 50 mM Hcy [34] in complete media for 24 h. In cotreatment group, cells were incubated with 50 mM Hcy and 50 mg/ml propolis [35] in complete media for 24 h.…”
Section: Experimental Groupingmentioning
confidence: 99%
“…The same group has also investigated the cytotoxic effect of ethanolic Tunisian propolis extract against cancer cell lines, HT-29 (the intestinal epithelial cell line), A549, Hep-2 (the human epithelial cell line), RAW 264.7, Vero (normal African green monkey kidney epithelial cell line) for 24 h where IC 50 values ranged from 15.7 to 200 μg/ml. Choudhari et al[15] studied cytotoxic effect of different concentrations (10, 25, 50, 100, 250 μg/ml) of EEP originating from India on four different cancer cell lines,…”
mentioning
confidence: 99%
“…Vatansever et al (2010) reported cytotoxicity of EEP at a concentration of 125 μg/mL to MCF-7 cell line also they found that cytotoxic effects of seven EEP samples collected from the same location is different. While, Choudhari et al (2013) found that IC 50 for ethanolic extract of propolis (EEP) of four cancer cell lines: human colon adenocarcinoma (HT-29), human epithelial colorectal adenocarcinoma (Caco-2), and murine melanoma cell lines (B16F1), MCF-7 to be 250 µg/mL. In another study, Campos et al (2014) reported that EEP promoted cytotoxic activity and primarily necrotic death in K562 erythroleukemia cells (Barzin et al, 2011;Campos et al, 2014).…”
Section: Resultsmentioning
confidence: 99%